AuroraX, PyAuroraX, and aurora-asi-lib: A user-friendly auroral all-sky imager analysis framework - Shumko, M.; Chaddock, D.; Gallardo-Lacourt, B.; Donovan, E.; Spanswick, E. L.; Halford, A. J.; Thompson, I.; Murphy, K. R. (Frontiers in Astronomy and Space Sciences, 2022)
Within the context of the Heliophysics System Observatory, optical images of the aurora are emerging as an important resource for exploring multi-scale geospace processes. This capability has never been more critical as we are on the cusp of a new era of geospace research, by which we mean studying the overall system as a system of systems. Historically, the patchwork of ground-based instrumentation has required customized solutions for accessing data, assessing data relevance, and then ultimately using each individual network alongside other assets. Here we introduce a new and comprehensive approach for data discovery and utilization for one type of data, namely auroral images. The AuroraX project (https://aurorax.space/) is a cyberinfrastructure platform for the discovery of scientific opportunities with access to optical auroral data. The program has broad objectives, so we focus on one key thread. In particular, we focus on describing the AuroraX platform and its API and web-based tools for all-sky imager (ASI) data. As a practical example, we demonstrate how to identify conjunctions using the AuroraX conjunction finder or PyAuroraX, a Python library that interfaces with the AuroraX platform. We then demonstrate how aurora-asi-lib, a Python library for interacting with and analyzing high-resolution ASI data, can be used for detailed conjunction analysis on a personal computer. Together, these tools enable a rapid and streamlined end-to-end exploration of auroral data.